Factors Affecting Da'wah Approaches Through the Islamic Tourism Management in Jordan - Lokman Mohammad Ibrahim Alokour
The current study aimed to identify the factors influencing advocacy trends through Islamic tourism management, and the most prominent of these factors that we will highlight is social media. It seeks to examine the relationship between the independent variables, namely, word-of-mouth (WOM), administrative arrangement, and online advertising, and the dependent variable, which is Islamic tourism in Jordan, to establish a strong understanding of the relationship between these variables. Furthermore, the study addresses in detail the dynamics of these factors, as well as the factors that influence them. The study adopts a descriptive-analytical approach and employs a questionnaire with four dimensions and six statements to measure demographic variables. A convenience sampling method is used to select a sample of 385 individuals from the study population. The survey was administered at a strategic location, the main international airport in the Capital city of Jordan, Amman. The Structural Equation Modeling (SEM) methodology is applied using the SPSS statistical analysis system to validate the proposed measurement model. Hypotheses are tested, and the relationship paths between the variables are analyzed, along with assessing the suitability of the assumed model based on field study data. Moreover, the factors that affect each independent variable are addressed. The findings of the study indicate a positive impact of word-of-mouth (WOM), administrative arrangements, and online advertising on Islamic tourism in Jordan. Key recommendations include implementing comprehensive social media campaigns and utilizing live streaming features to attract tourists to visit Jordan, supporting digital influencers in disseminating Islamic, as well as developing multilingual content about Islamic tourism It is also recommended for future researchers to explore the potential of social media as a catalyst for promoting Islamic tourism in Jordan, by using this study to obtain a comprehensive understanding of Islamic tourism dynamics in Jordan